Transformation Of The Role Of Accounting Information Systems In Managing Financial Complexity - Permana, Galih Dika; Deanidia, Tiffany; Supratikta, Hadi (Indonesian Development of Economics and Administration Journal, 2024)
This research aims to explore the impact of accounting information system transformation on efficiency, accuracy and innovation in business financial management. Apart from that, this research also aims to understand the challenges and opportunities that arise during this transformation process. This research uses a qualitative and quantitative approach by conducting a literature review of various relevant studies regarding the transformation of accounting information systems. Data were analyzed through descriptive and synthetic approaches to evaluate the main findings from previous studies. The research results show that the transformation of accounting information systems has a significant impact in increasing efficiency, accuracy and innovation in business financial management. Digitalization plays a key role in speeding up business processes, increasing transparency and providing better access to financial information. Even though there are challenges in implementing and using accounting information systems, the long-term benefits are very important for companies in achieving financial goals and facing increasingly complex market challenges in this digital era. This research provides a deeper understanding of the importance of accounting information system transformation in managing the complexity of business finances in this digital era, as well as identifying challenges and opportunities that need to be overcome in the transformation process.